Structure of the Baryon Halo Around a Supermassive Primordial Black Hole - Boris Murygin; Viktor Stasenko; Yury Eroshenko (Particles, 2024)
According to some theoretical models, primordial black holes with masses of more than 108 solar masses could be born in the early universe, and their possible observational manifestations have been investigated in a number of works. Dense dark matter and baryon halos could form around such primordial black holes even at the pre-galactic stage (in the cosmological Dark Ages epoch). In this paper, the distribution and physical state of the gas in the halo are calculated, taking into account the radiation transfer from the central accreting primordial black hole. This made it possible to find the ionization radius, outside of which there are regions of neutral hydrogen absorption in the 21 cm line. The detection of annular absorption regions at high redshifts in combination with a central bright source may provide evidence of the existence of supermassive primordial black holes. We also point out the fundamental possibility of observing absorption rings with strong gravitational lensing on galaxy clusters, which weakens the requirements for the angular resolution of radio telescopes.